Quantification of prolactin (PRL) and PRL receptor messenger RNA in gilthead Seabream (Spares aurata) after treatment with Estradiol-17 beta - Cavaco, J. E. B. (2014)
Prolactin (PRL) in fish is considered to be an osmoregulatory hormone, although some studies suggest that it may influence the production of steroid hormones in the gonads. The objective of the present study was to establish if PRL is involved in reproduction of the gilthead seabream—a protandrous hermaphrodite. Adult and juvenile gilthead seabream received implants of estradiol-17b (E2) for 1 wk during the breeding season, and the mRNA expressions of PRL and PRL receptor (sbPRLR) were determined. Northern blot analysis revealed a single pituitary PRL transcript, the expression of which was significantly reduced by E2 treatment in adults but significantly increased in juvenile fish. In adult gonads, four sbPRLR transcripts of 1.1, 1.3, 1.9, and 2.8 kilobases were observed. A competitive reverse transcription-polymerase chain reaction was developed and used to determine how E2 treatment alters expression of the gonadal sbPRLR gene. Seabream PRLR was detectable in all samples analyzed by this assay. Levels of sbPRLR mRNA increased significantly (50-fold) after E2 treatment in adults, but a 24-fold decrease was measured in juveniles. Immunohistochemistry using specific polyclonal antibodies raised against an oligopeptide from the extracellular domain of sbPRLR detected the receptor in spermatogonia and oocytes. Taken together, the preceding results suggest that in the seabream, PRL may act on both testis and ovary via its receptor and that the stage of maturity influences this process. The full characterization and relative importance of the different transcripts of sbPRLR in eliciting the action of PRL in the gonads remain to be elucidated.